Casticin promotes osteogenic differentiation of bone marrow stromal cells and improves osteoporosis in rats by regulating nuclear factor‐κB/mitogen‐activated protein kinase. (4th October 2022) - Zhang, Dong; Li, Xuejia; Li, Jianmin; Liu, Wanxin; Yu, Ying; Wang, Shuqiang; Ye, Xiaojian
Abstract: Background: Osteoporosis has influenced millions of people, especially postmenopausal women, which has become a big burden to the whole world. Although the diverse roles of casticin (CAS) on different diseases were identified, whether it was implicated with osteoporosis was unknown. Methods: A rat model of osteoporosis was established through dexamethasone (DEX) treatment and a cell model reflecting the osteogenic and osteoclast induction was constructed in bone marrow stromal cells (BMSCs). The calcification at the late stage of induction was measured via Alizarin Red S staining. Western blot was applied to evaluate the levels of proteins. Results: Hematoxylin and eosin staining revealed that the number of bone trabecular in DEX‐induced osteoporosis rats was decreased, while increased doses of CAS treatment elevated the number of bone trabecular. CAS treatment alleviated DEX‐induced osteoporosis in rats. Moreover, we found that CAS inhibited the nuclear factor‐κB/mitogen‐activated protein kinase (NF‐κB/MAPK) pathway. In addition, CAS promoted osteogenic differentiation of BMSCs and reduced osteoclastogenesis of bone marrow monocytes. Finally, CAS was observed to retard the receptor activator of NFκ‐B ligand‐induced NF‐κB/MAPK pathway. Conclusion: CAS promoted osteogenic differentiation of BMSCs and improved osteoporosis in rats by regulating the NF‐κB/MAPK pathway. This might shed a light into using CAS as a drug treating osteoporosis in the future.